2014
DOI: 10.1017/s1368980014001153
|View full text |Cite
|
Sign up to set email alerts
|

The impact of restaurant consumption among US adults: effects on energy and nutrient intakes

Abstract: Objective: To examine the effect of fast-food and full-service restaurant consumption on adults' energy intake and dietary indicators. Design: Individual-level fixed-effects regression model estimation based on two different days of dietary intake data was used. Setting: Parallel to the rising obesity epidemic in the USA, there has been a marked upward trend in total energy intake derived from food away from home. Subjects: The full sample included 12 528 respondents aged 20-64 years who completed 24 h dietary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
89
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(89 citation statements)
references
References 25 publications
0
89
0
Order By: Relevance
“…Furthermore, those that eat food away from home consume approximately 200 more kilocalories per day, regardless of whether the restaurant is fast food or full service (4,5). These consumption patterns concur with disparities in childhood obesity across racial/ethnic groups in that African Americans consume more of their calories away from home than other racial groups (5,6). …”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…Furthermore, those that eat food away from home consume approximately 200 more kilocalories per day, regardless of whether the restaurant is fast food or full service (4,5). These consumption patterns concur with disparities in childhood obesity across racial/ethnic groups in that African Americans consume more of their calories away from home than other racial groups (5,6). …”
Section: Introductionmentioning
confidence: 57%
“…This result aligns with the findings of other studies that demonstrate lower availability of healthy food options in minority neighborhoods or areas (812,24). As previously noted, blacks eating food away from home consumed more calories than other racial groups also consuming food away from home (6). It was clear from our study that CMA scores were low throughout the region and significantly lower in black block groups than in white and mixed-race block groups.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…They have commonly reported a higher energy contribution of fat from commercially-prepared meals, specifically compared with that from food prepared at home. Current evidence from studies on American adults has also revealed a positive association between fast-food and full-service restaurant consumption and intakes of sodium and fat [3435]. Additionally, research performed in Western countries has consistently reported a negative impact of frequent consumption of food away food home on health.…”
Section: Discussionmentioning
confidence: 99%
“…In Canada, around one quarter of adults eat food prepared in a fast food restaurant each day (Garriguet, 2004). Food eaten outside the home is associated with higher calorie and fat intake, and excess weight gain (Brownell, 2004, Dietary Guidelines Advisory Committee (DGAC), 2010, Mancino et al, 2009, Nguyen and Powell, 2014, Pereira et al, 2005). A primary challenge to healthy eating in restaurant settings is that consumers have very little idea about the nutritional quality of menu items, which varies widely even for similar items across different establishments (Block et al, 2013, Burton et al, 2006, Scourboutakos and L'Abbé, 2012).…”
Section: Introductionmentioning
confidence: 99%